1996
DOI: 10.1016/0735-1097(96)00173-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of precordial ST segment depression on admission electrocardiogram in patients with inferior wall myocardial infarction

Abstract: The risk of mortality is higher in patients with an inferior myocardial infarction and maximal ST segment depression in precordial leads V4 to V6 versus precordial leads V1 to V3 on the admission ECG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Terminal QRS distortion on the admission ECG, as originally described by Birnbaum,1) is associated with larger infarcts and increased mortality in patients undergoing reperfusion therapy for STEMIs. The mechanisms of the terminal QRS distortion are explained by a prolongation of the electrical conduction in the Purkinje fibers in the ischemic region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Terminal QRS distortion on the admission ECG, as originally described by Birnbaum,1) is associated with larger infarcts and increased mortality in patients undergoing reperfusion therapy for STEMIs. The mechanisms of the terminal QRS distortion are explained by a prolongation of the electrical conduction in the Purkinje fibers in the ischemic region.…”
Section: Discussionmentioning
confidence: 99%
“…R ecently, it has been reported that large infarcts are associated with terminal QRS-distortion in patients with ST-elevation myocardial infarctions (STEMIs), [1][2][3][4] and that the ECG pattern of the distortion of the terminal portion of the QRS complex is an independent predictor of the prognosis in STEMI patients, and has a better correlation to the infarct size than the magnitude of the ST segment elevation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21][22][23][24][25][26] According to Peterson et al 25 , there is marginal correlation of magnitude of precordial depression of ST segment with the magnitude of elevation of ST segment in inferior AMI. Contrary to the above narrated studies, we observed that multivessel disease was more common in patients having depression of ST segment in leads V4-6 (83.6%) compared to 56.8% in Group I (V1-3) with acute inferior MI thus indicating the association of depression of ST segment in anterior leads with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…It is clinically relevant because these patients have the best overall outcome of all sub-groups of IWMI. In addition, these patients have less myocardial damage as measured by lower peak CK values, and lower rates of heart failure, cardiogenic shock, and dysrhythmias (2,8). Peterson et al report in-hospital mortality rates of 3.2% in those patients without reciprocal changes, and 4.7% with reciprocal changes.…”
Section: Iwmi Without Reciprocal Changesmentioning
confidence: 96%